International Patients on Operation Vacation - Perspectives of Patients Travelling to Hungary for Orthopaedic Treatments - Eszter Kovacs; Gabor Szocska; Cécile Knai (Kerman University of Medical Sciences, 2014)
Background The importance of cross-border healthcare, medical and health tourism plays a significant role in the European health policy and health management. After dentistry, orthopaedic treatments are the leading motivation for seeking care in Hungary, as patients with rheumatic and motion diseases are drawn to the thermal spas and well-established orthopaedic centres. This paper aims to gain insight into foreign patients' perspectives on their experience of having sought medical tourism in orthopaedic care in Hungary. Methods A patient survey was conducted in 2012 on motivations for seeking treatment abroad, orthopaedic care received and overall satisfaction. In addition, health professionals' interviews, and 17 phone interviews were conducted in 2013 with Romanian patients who had orthopaedic treatment in Hungary. Finally, medical records of foreign patients were analysed. Results The survey was completed by 115 participants - 61.1% females, mean age= 41.9, 87% Romanian origin. Most of the patients came to Hungary for orthopaedic surgeries, e.g. arthroscopy, knee/hip prosthesis or spinal surgery. 72.6% chose Hungary because of related to perceived better quality and longstanding culture of Hungarian orthopaedic care. Over 57% of patients reported being 'very satisfied' with care received and 41.6% 'satisfied'. The follow-up interviews further reflected this level of satisfaction, therefore many respondents stating they have already recommended the Hungarian healthcare to others. Conclusion Based on the findings, patients from neighbouring regions are increasingly seeking orthopaedic care in Hungary. Patients having orthopaedic care are highly satisfied with the quality of care, the whole treatment process from the availability of information to discharge summaries and would consider returning for further treatments.